Estudio de revisión de tipologías de sistemas de muros industrializados en Bogotá (2017)
Currently in Colombia the use of industrialized structural walls has been increasing. This is due to all the economic benefits they bring to builders and investors. However, in the last earthquakes presented around the world Chile in 2010 and New Zealand 2011 have revealed a series of failures in the buildings that use the walls as a structural system. The purpose of this project is to carry out an analysis that allows a qualitative and approximate way to determine how the seismic behavior of construction projects with industrialized walls in Bogotá. In addition, find representative projects of the city of Bogota for future studies. For this, information from different design offices of the city will be collected and a summary of the project variables will be generated. Then, a study of these variables will be done to see which projects have the most common characteristics and thus to select the representative group...